Commission for the Upper Cauca River Basin Recovery, Collaborative Governance for Sustainability and Water Security - Sánchez Torres, Luis Dario; Galvis Castaño, Alberto; Gandini, Mario Andres; Almario, Gloria; Montero, Maria Victoria; Vergara, María Virginia (Frontiers in Water, 2022)
Rivers are essential for life, there is an indissoluble relationship between the natural system and the human system. Aquatic ecosystems guarantee ecosystem services to the human system, on the other hand, the human system makes use of these services and as a result of this generates effects on the natural system. However, an over use of these services could adversely impact the natural system. Therefore, the recovery of rivers is a priority for the planet. This work describes the progress of the Commission for the recovery of the upper Cauca river basin as a collaborative governance for sustainability and water security in the region. The upper basin is between the Colombian massif in the department of Cauca and the municipality of Cartago in Valle del Cauca. It is an important natural, cultural, social, and economic resource of Colombia, but it presents a continuous deterioration of water availability, both in quantity and quality, limiting its use for human consumption and a reduction in biodiversity. This work shows that the Commission for the upper Cauca river basin recovery is a process in development. The Commission is an instance made up of public and private entities, which arises from the failure of the current model of water resource management in Colombia. The central problem is how to transcend short-term planning in administrations to long-term planning based on a shared vision. Collaborative governance is proposed as a recovery of the Cauca river based on the concept of bioculturality and the rights of nature, due to the deep relationship of unity between nature and the human species. The need to achieve a shared vision is highlighted, to act under the watershed vision with all the actors involved. In addition, minimal and conclusive indicators must be defined that society recognizes and that motivates it to advance in the recovery. The aquatic ecosystems recovery is a priority, understanding that the investments required for achieving this goal can also significantly contribute to sustainability and water security for the region.